New strategies to tackle diabetic kidney disease. Issue 4 (July 2016) - Batu Demir, Duygu; Cooper, Mark E.
Abstract : Purpose of review: The purpose of this review is to provide an overview of recent preclinical and clinical studies, which demonstrate new insights for the treatment of diabetic kidney disease (DKD) and to outline future directions with respect to novel therapies. Recent findings: Positive findings with respect to new glucose-lowering agents such as sodium-dependent glucose transporter 2 inhibitors may lead to a change in the way we treat diabetic individuals with or at risk of DKD. Additional positive phase 2 clinical studies with drugs that have hemodynamic actions such as endothelin antagonists and mineralocorticoid receptor antagonists have led to larger phase 3 trials with atrasentan and finerenone, respectively, in order to address if these drugs indeed delay the development of end-stage renal disease. A number of other pathways are currently under active preclinical investigation and hopefully over the next decade will lead to promising drug candidates for subsequent clinical trials. Summary: DKD remains an area of active preclinical and clinical investigation. Positive results with some of the more promising agents should lead to strategies to reverse, attenuate or prevent DKD.